Analysis and design of the Integrated Sistem Pemantauan Agensi Awam (ISPAAA) - Ali, Haddadi (2014)
Monitoring is an important process used to track work progress in a project. It is also to avoid delay of a construction project. This study explores the monitoring methods of project progress used by the contractors in a private project which is Sekolah Islam Hidayah, Johor Bahru. In this study, the key elements in work scheduling used for project monitoring are identified through the use of Microsoft Project software. Besides that, comparison of monitoring methods used by private project and government project is done. Factors that cause changes of work scheduling are also identified through physical monitoring. Therefore, Microsoft Project has been used as a tool in scheduling and effective monitoring. Meanwhile, physical monitoring on site project is done to monitor the project progress and photos are also taken for the work progress record. From this study, there are three elements in work scheduling which helps in monitoring which are tasks, time and progress line. Financial S-Curve (Cost versus Time) is generated to track the project progress and percentage of work done has been recorded from the analysis of S-Curve. From the comparison of work monitoring used by private and government project, it has shown that both of them have their owned Standard Operation Procedure used as a project monitoring method. Through physical monitoring, the factors that causes changes of work schedule are identified which are include lack of materials, amendment of design, unpredictable weather condition and lack of financial resources. In conclusion, this study has shown that monitoring methods are a basis part in order to control project activities and to avoid risks of delay in a construction project.